PERAN PEMERINTAH DESA DALAM PENGELOLAAN PROGRAM USAHA PENGELOLAAN PUPUK ORGANIK (UPPO) DI DESA KOLAI KECAMATAN MALUA KABUPATEN ENREKANG - Ariyawan Alfayed Martmono; Mappamiring Mappamiring; Ihyani Malik (Department of Government Studies Universitas Muhammadiyah Makassar, 2013)
This study aimed to determine the role of the sub-district government in managing the UPPO program. The results of this study were expected as the input for the Kolai sub-district government in performing their duties and functions as the spearhead of Indonesian government. Academically, the results of this study were expected to provide more values which can then be compared with other scientific research, particularly the study under the problem of the role of sub-district government. This was a descriptive quantitative research, basically, this was a survey study and samples in this study were 35 people by purposive sampling technique . Data were collected by using techniques such as observation, questionnaires and developed interviews for the respondent . The data were analyzed by descriptive quantitatively, in which all the data collected by the authors, and then presented in the form of frequency tabulation completed by the responds of respondents obtained from informants , interviews , and questionnaires . The results showed an active role of sub-district government in managing UPPO program that can influence the community participation in UPPO management. By the support and assist of the sub-district government, UPPO management program can run well. Moreover, the support and assist of the sub-district government towards UPPO program management were 1. Facilitate the UPPO program 2. Facilitate meetings between the representatives agricultural services and society as of manager UPPO program 3 . Carrying out training . Penelitian ini bertujuan untuk mengetahui peranan pemerintah desa dalam pengelolaan program UPPO. Hasil dari penelitian ini diharapkan menjadi masukan bagi pemerintah desa kolai dalam menjalankan tugas dan fungsinya sebagai ujung tombak pemerintahan Indonesia. Dari segi akademik, hasil dari penelitian ini diharapkan memberi nilai tambah yang selanjutnya dapat dikomparasikan dengan penelitian-penelitian ilmiah lainnya, khususnya yang mengkaji masalah peranan pemerintah desa. Penelitian ini adalah Deskriptif kuantitatif, dasar penelitian yang digunakan adalah survey dan sampel dalam penelitian ini sebanyak 35 orang menggunakan teknik purposive sampling. Data dikumpulkan dengan menggunakan teknik berupa observasi, kuesioner serta dikembangkan dengan wawancara kepada responden. Data tersebut dianalisis secara Deskriptip kuantitatif yaitu menganalisis semua data yang berhasil dikumpulkan penulis, dan selanjutnya disajikan dalam bentuk tabulasi frekuensi dilengkapi dengan tanggapan responden yang diperoleh dari hasil Informan, wawancara, dan kuesioner. Dari hasil penelitian menunjukkan peran aktif aparat pemerintah desa dalam pengelolaaan program UPPO dapat berpengaruh terhadap partisipasi masyarakat dalam pengelolaan UPPO. Dengan adanya dukungan dan bantuan dari pemerintah desa maka pengelolaan program UPPO dapat berjalan lancar. Adapun bentuk dukungan dan bantuan pemerintah desa dalam pengelolaan program UPPO adalah (1). Memfasilitasi pengadaan program UPPO (2). Memfasilitasi pertemuan utusan dinas pertanian dengan msyarakat pengelola program UPPO (3). Melakukan pembinaan.